Production of C3+ Olefins and Propylene from Ethanol by Zr-Modified H-ZSM-5 Zeolite Catalysts - Megumu Inaba; Kazuhisa Murata; Isao Takahara; Ken-ichiro Inoue (Advances in Materials Science and Engineering)
Ethanol conversion to C3+ olefins, especially propylene, using Zr-modified H-ZSM-5 catalysts was investigated. Zr-modification to H-ZSM-5 zeolite could improve the initial yield of C3+ olefins and propylene and could reduce the initial yield of ethylene. In general, catalysts exhibiting the higher initial yield of propylene showed the steeper decrease in propylene yield as the reaction proceeded. However, Zr-modification to H-ZSM-5 could depress the decrease in propylene yield for aqueous ethanol. As cause of catalytic deactivation, carbon deposition on catalyst and framework collapse of zeolite support can be considered. The addition of water to Zr-modified H-ZSM-5 catalyst could depress carbon deposition in some degree, and, as a result, the decrease in propylene yield could be depressed.